2020
DOI: 10.1111/birt.12479
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes of fetal macrosomia and risk of stillbirth among term deliveries over the previous four decades

Abstract: Objectives To evaluate the association between macrosomia and stillbirth over the previous four decades and to determine the consistency of the relationship. Methods This was a population‐based retrospective cohort study using United States Natality and Fetal Death Data from 1982 to 2017 and restricted to the gestational age range of 37‐41 weeks inclusive. Macrosomia was defined as birthweight ≥4000 g and subdivided into its grades as previously recommended: grade 1 (4000‐4499 g), grade 2 (4500‐4999 g), and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Macrosomia was defined as weight >4000 g and further divided into subgroups of grade one -4000-4499g, grade 2 -4500-4999 g, and grade 3 ->5000 g. The authors observed a substantial fall in stillbirth rates during the study period in both macrosomic and normal weight fetuses. Grade 1 macrosomia was not a stillbirth risk factor (0,95 stillbirths per 1000 pregnancies), while grade 2 macrosomia increased the risk 2 fold (2,43/1000) and grade 3 had a stillbirth rate (13,03/1000) -similar to that of low birthweight fetuses (15.54/1000) [34].…”
Section: Stillbirthmentioning
confidence: 89%
“…Macrosomia was defined as weight >4000 g and further divided into subgroups of grade one -4000-4499g, grade 2 -4500-4999 g, and grade 3 ->5000 g. The authors observed a substantial fall in stillbirth rates during the study period in both macrosomic and normal weight fetuses. Grade 1 macrosomia was not a stillbirth risk factor (0,95 stillbirths per 1000 pregnancies), while grade 2 macrosomia increased the risk 2 fold (2,43/1000) and grade 3 had a stillbirth rate (13,03/1000) -similar to that of low birthweight fetuses (15.54/1000) [34].…”
Section: Stillbirthmentioning
confidence: 89%
“…We used joinpoint regression, which is a modeling technique, to detect the change in the rate of events over time. [16] We also calculated the average annual percentage change (AAPC) for trends in rates of viable pregnancies, live birth and stillbirth in both child and teen mothers over the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional fetal mortality rates are expressed as deaths per 1000 total births, while fetuses-at-risk rates are expressed per 1000 fetuses at risk of mortality. This technique has been recommended as a more sensitive approach to understand the intersection of birthweight-specific and gestational age-specific perinatal mortality risks [8,9]. Adjusted Cox proportional-hazards regression models measuring the association between maternal nativity and stillbirth for the entire study population and among various racial/ethnic groups were created.…”
Section: Discussionmentioning
confidence: 99%